Propulsive asymmetry in lower limbs and force time-course during the push in vertical jumps: different skiing disciplines - Minetti, A. E.; Seminati, E. (Abstractband der 6. Internationalen Konferenz Wissenschaft und Skisport. 14.-19. Dezember 2013, St. Christoph am Arlberg, Österreich, 2013)
This is the first attempt to analyze the explosive vertical jump, across the different skiing disciplines, according to the force pattern and the separate contribution of lower limbs, with the underlying hypothesis that equal pushes, in terms of amount and timing, would enhance the overall performance.